Rządy prawa. Uwagi o znaczeniu i ewolucji pojęcia - Supernat, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This article offers an analysis of the rule of law including its multiplicity of meanings, evolution and functions. The analysis confirms that the rule of law is an exceedingly elusive concept. However, its main role is unquestionable: it operates to ensure that governmental power is not abused.
Keywords: the rule of law; principles; administration; European Union